EVALUATION TRIGGERS FOR EXACERBATION ACUTECHRONIC OBSTRUCTIVE PULMONARY DISEASE PATIENT SADMITTED DEPARMENT OF EMERGENCY MEDICINETHONG NHAT HOSPITAL - Bảo Huy, Lê; Chánh, Vũ Đình (Journal of Health and Aging, 2025)
Exacerbations of Chronic Obstructive Pulmonary Disease (COPD) lead to decline in lung function, quality of life, and increased costs and mortality. Identifying trigger factors for exacerbations, especially in elderly patients with comorbidities, is crucial due to limited research in Vietnam. To investigate trigger factors for COPD exacerbations in patients admitted to the Emergency Department of Thong Nhat Hospital, HCMC. A prospective, cross-sectional descriptive study was conducted on 95 patients admitted to the Emergency Department of Thong Nhat Hospital for COPD exacerbation from January 2020 to July 2020. The mean age was 75.39 years; 91.6% were male, and 60% of patients had ≥2 exacerbations per year. Common cardiovascular comorbidities included hypertension (85.3%) and coronary artery disease (41.1%). Multiple factors (cardiovascular disease, bronchiectasis, Asthma-COPD Overlap (ACO), smoking, non-compliance with treatment) were associated with more frequent and severe exacerbations. Importantly, infection and eosinophilia (≥300 cells/µL or ≥2%) were statistically significantly associated with exacerbations (p < 0.05). Patients with COPD exacerbation were predominantly elderly males, often with cardiovascular comorbidities. Infection and eosinophilia were factors statistically significantly associated with exacerbations.